Hubungan antara Kecerdasan Kinestetik dan Kepercayaan Diri Siswa dengan Hasil Belajar Tari Piring Pada Siswa Kelas VIII di SMP Regina Pacis Bogor - Ariandini; Triana, Dinny Devi; Suwandi, Tuteng (Jurnal Pendidikan Tari, 2024)
This study aims to find out how big the relationship is between Kinesthetic Intelligence and Student Confidence with Dance Learning Outcomes. This study uses a quantitative research method with a correlational research design. The data collection technique used the Stratified Random Sampling technique with a total population of 215 students and a sample of 139 students. The results showed that: (1) There is a relationship between kinesthetic intelligence and learning outcomes of the Plate dance with the Pearson Correlation showing 0.149 and a determination coefficient of 82% (2) There is a relationship between self-confidence and learning outcomes of the Plate dance with the Pearson Correlation showing 0.497 and coefficient of determination of 81% (3) There is a significant relationship between kinesthetic intelligence and self-confidence of 0.002 <0.05 with a positive correlation and a coefficient of determination of 68% (4) There is a relationship between X1 and X2 with Y, the results of the study are simultaneously known coefficient of determination of 84%. Kinesthetic intelligence and student self-confidence influence each other and can contribute to the learning outcomes of plate dance in class VIII students at SMP Regina Pacis Bogor. Keywords: Kinesthetic Intelligence, Confidence, Learning Outcomes, Plate Dance.